(untitled) (Global Journal of Management and Business Research, 2022)
This article focuses on the financial performance measures used by manufacturing small and medium enterprises (SMEs) in Pretoria, South Africa. The objectives were to identify the financial tools that are used by SMEs to measure their financial performance, and recommend improvements (if any) and training interventions that would possibly be needed to measure financial performance successfully. Semi-structured interviews were conducted with SME owners. Most of the respondents use financial ratios when measuring their financial performance, although to a limited extent. None of the respondents use bankruptcy prediction models. SMEs could benefit from using ratios that have been proven to be the best financial measures as well as the ratios that have worked well for most of the participants. Bankruptcy prediction models known to many of the participants as well as financial software packages should also be considered as they might enhance the success rate of SMEs.